2010
DOI: 10.2353/ajpath.2010.090775
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial Cells Get Side-Tracked

Abstract: Like stem cells, a subpopulation of cancer cells is characterized by the property of self-renewal, unlimited and high proliferative potential, expression of multidrug-resistance proteins, active DNA repair capacity, apoptosis resistance, and an enormous developmental plasticity. 1Based on these observations, the concept of cancer stem cells has been developed, which proposes that tumor-initiating cancer cells may either originate from normal stem cells, or that cancer cells may undergo progressive de-different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Successful silencing of Syndecan-1 in Syndecan-1 siRNA vs control siRNA-transfected MDA-MB-231 cells was confirmed by flow cytometry ( Figure 1A ). We next investigated the SP phenotype, a surrogate marker for putative stem cell activity based on the ability of effluxing the fluorescent dye Hoechst 33342 via ABC transporters [ 20 , 21 ], in the Syndecan-1-depleted cells. Hoechst 33342 dye exclusion assays revealed that Syndecan-1 siRNA transfected cells contained on average 0.62% (±0.36%) SP cells, whereas control cells contained 1.55% (±0.65%) SP cells ( Figure 1B ), corresponding to a significant >60% relative decrease of the SP upon Syndecan-1 depletion (p<0.01, n=3) ( Figure 1E ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Successful silencing of Syndecan-1 in Syndecan-1 siRNA vs control siRNA-transfected MDA-MB-231 cells was confirmed by flow cytometry ( Figure 1A ). We next investigated the SP phenotype, a surrogate marker for putative stem cell activity based on the ability of effluxing the fluorescent dye Hoechst 33342 via ABC transporters [ 20 , 21 ], in the Syndecan-1-depleted cells. Hoechst 33342 dye exclusion assays revealed that Syndecan-1 siRNA transfected cells contained on average 0.62% (±0.36%) SP cells, whereas control cells contained 1.55% (±0.65%) SP cells ( Figure 1B ), corresponding to a significant >60% relative decrease of the SP upon Syndecan-1 depletion (p<0.01, n=3) ( Figure 1E ).…”
Section: Resultsmentioning
confidence: 99%
“…Side population (SP) analysis has been shown to enrich breast CSCs [ 19 ]. The SP can be identified by flow cytometry based on their property of effluxing the fluorescent dye Hoechst 33342 via ATP-binding cassette transporter proteins such as ABCG/Brcp1 [ 3 , 20 , 21 ]. Furthermore, breast CSCs can be isolated based on expression of CD44(+)/CD24(-/low), and aldehyde dehydrogenase activity (ALDH1+) [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, although the exact mechanism of progression and metastasis in endometrial cancer remains largely unknown, it is worth noting that ECSCs have been identified in endometrial cancer tissues [ 30 - 34 ] and considered to be an engine of tumor evolution [ 35 - 38 ]. In this study, we performed enriched ECSCs by serum-free suspension cultivation.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence indicate that the aggressive phenotype of IBC is due to enrichment for chemo- and radioresistant cancer stem cells (CSCs) [ 13 ]. These cells are characterized by self-renewal, unlimited and high proliferative potential, expression of multidrug-resistance proteins, efficient DNA repair capacity and apoptosis resistance [ 14 , 15 ]. Using flow cytometry, CSCs can be distinguished from the bulk of the tumor by their expression of cell surface makers CD44 and CD24 (as a CD44 (+) CD24 (-/low) subpopulation) and based on the activity of ALDH1 [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Using flow cytometry, CSCs can be distinguished from the bulk of the tumor by their expression of cell surface makers CD44 and CD24 (as a CD44 (+) CD24 (-/low) subpopulation) and based on the activity of ALDH1 [ 16 ]. Due to their functional link to therapeutic resistance, CSCs represent an attractive therapeutic target to dampen tumor recurrence [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%